Control of carbon content in amorphous GeTe films deposited by plasma enhanced chemical vapor deposition (PE-MOCVD) for phase-change random access memory applications. (3rd June 2015) - Aoukar, M; Szkutnik, P D; Jourde, D; Pelissier, B; Michallon, P; Noé, P; Vallée, C
Abstract: Amorphous and smooth GeTe thin films are deposited on 200 mm silicon substrates by plasma enhanced—metal organic chemical vapor deposition (PE–MOCVD) using the commercial organometallic precursors TDMAGe and DIPTe as Ge and Te precursors, respectively. X-ray photoelectron spectroscopy (XPS) measurements show a stoichiometric composition of the deposited GeTe films but with high carbon contamination. Using information collected by Optical Emission Spectroscopy (OES) and XPS, the origin of carbon contamination is determined and the dissociation mechanisms of Ge and Te precursors in H2 + Ar plasma are proposed. As a result, carbon level is properly controlled by varying operating parameters such as plasma radio frequency power, pressure and H2 rate. Finally, GeTe films with carbon level as low as 5 at. % are obtained.